Potensi Antibakteri Staphylococcus Aureus dan Escherichia Coli dari Ekstrak Kasar Bakteri Asosiasi Karang Batu yang Terinfeksi Penyakit Brown Band (Brb) - Funty Septiyawati (Universitas Sulawesi Barat, 2020)
The increasing number of cases of pathogenic bacteria resistant to antibiotics has recently triggered an increasing search for sources of new antimicrobial compounds. One of the potential sources of producing antimicrobial compounds is bacteria associated with corals infected with the disease. This study aimed to obtain a bacterial extract associated with corals that have the antimicrobial activity of S. aureus and E. coli. This study used 3 isolates of association bacteria types Pseudomonas sp, Flavobacterium sp, and Bacillus sp. The results of initial screening with the High Throughput Screening (HTS) method only extracts of the bacteria isolate Flavobacterium sp which have antibacterial activity, then the results of diffusion tests show the potential for Staphylococcus aureus with a clear zone diameter of 0.7 mm, while the Escherichia coli bacteria have no activity